Blockchain and Holochain in Medical Education from Planetary Health and Climate Change Perspectives - Yavuz Selim Kıyak (Universidad de Murcia, 2023)
As we are transitioning from the age of information to the age of artificial intelligence, this study aims to explore the potential of blockchain and Holochain technologies as solutions to the data privacy, security, and integrity concerns in medical education, and to provide recommendations for their use that also minimize negative impacts regarding planetary health and climate change. While these technologies offer promising solutions, their environmental impact has not been discussed in the literature with regards to medical education. This study offers two key recommendations for medical education researchers, educators, and policy makers to ensure the responsible use of Web3 technologies in this field. Recommendation 1: If the use of blockchain technology is necessary, avoid using proof-of-work blockchains. Recommendation 2: Use Holochain instead of blockchain.